Artery Wall Assessment Helps Predict Kidney Transplant Outcome - Hernández, Domingo; Triñanes, Javier; Salido, Eduardo; Pitti, Sergio; Rufino, Margarita; González-Posada, José Manuel; Torres, Armando (PloS one, 2015)
Kidney transplant recipients have high cardiovascular risk, and vascular inflammation may play an important role. We explored whether the inflammatory state in the vessel wall was related to carotid intima-media thickness (c-IMT) and patient survival following kidney transplantation. In this prospective observational cohort study we measured c-IMT and expression of proinflammatory cytokines and adhesion molecules in the inferior epigastric artery in 115 kidney transplant candidates. Another c-IMT measurement was done 1-year post-transplantation in 107. By stepwise multiple regression analysis we explored factors associated with baseline c-IMT and their changes over time. Multivariate Cox regression analysis was constructed to identify risk factors for mortality. A worse cardiovascular profile (older age, smoker, diabetic, carotid plaque, systolic blood pressure and vascular calcification) and higher VCAM-1 levels were found in patients in the highest baseline c-IMT tertile, who also had a worse survival. Factors independently related to baseline c-IMT were age (β=0.369, P<0.0001), fasting glucose (β=0.168, P=0.045), smoking (β=0.228, P=0.003) and VCAM-1 levels (β=0.244, P=0.002). Independent factors associated with c-IMT measurement 1-year post-transplantation were baseline c-IMT (β=-0.677, P<0.0001), post-transplant diabetes (β=0.225, P=0.003) and triglycerides (β=0.302, P=0.023). Vascular VCAM-1 levels were associated with increased risk of mortality in bivariate and multivariate Cox regression. Notably, nearly 50% of patients showed an increase or maintenance of high c-IMT 1 year post-transplantation and these patients experienced a higher mortality (13 versus 3.5%; P=0.021). A worse cardiovascular profile and a higher vascular VCAM-1 protein levels at time of KT are related to subclinical atheromatosis. This could lead to a higher post-transplant mortality. Pre-transplant c IMT, post-transplant diabetes and triglycerides at 1-year post-transplantation may condition a high c-IMT measurement post-transplantation, which may decrease patient survival.